2019
DOI: 10.3389/fpls.2018.02001
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes and Vertical Distribution of Fine Root Biomass During Vegetation Restoration in a Karst Area, Southwest China

Abstract: In karst ecosystems, plants absorbing smaller amounts of nutrients, owing to shallow soil, show limited growth. In addition, fine roots (diameter < 2 mm) contribute to the regulation of nutrient cycles in terrestrial ecosystems. However, the spatial and temporal variations of fine root biomass in different vegetation types of the karst region remains poorly understood. In this study, we investigated the seasonal and vertical variation in biomass, necromass, and total mass of fine roots using sequential soil co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 44 publications
4
28
0
Order By: Relevance
“…Soil erosion, the main process of soil erosion export, occurs naturally but is accelerated by human activities. The physical reservoir of carbon held in soil aggregates could be destroyed by soil erosion (Yue et al, 2016;Deng et al, 2018), resulting in a decrease in effective root depth, nutrient availability and water holding capacity in the root zone (Yang et al, 2003;Du et al, 2019). Soil erosion removes considerable quantities of topsoil, which will greatly influence soil nutrient stocks and will impact soil nutrient redistribution and global biochemistry (Quinton et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Soil erosion, the main process of soil erosion export, occurs naturally but is accelerated by human activities. The physical reservoir of carbon held in soil aggregates could be destroyed by soil erosion (Yue et al, 2016;Deng et al, 2018), resulting in a decrease in effective root depth, nutrient availability and water holding capacity in the root zone (Yang et al, 2003;Du et al, 2019). Soil erosion removes considerable quantities of topsoil, which will greatly influence soil nutrient stocks and will impact soil nutrient redistribution and global biochemistry (Quinton et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…During the past century, a large part of the karst region in southwest China was severely degraded following the destruction of natural vegetation due to human disturbance. Thankfully, most of the degraded land has been undergoing ecological restoration, either through natural regeneration or afforestation, attributed to the implementation of ecological restoration projects (e.g., the "Grain for Green" project, the Karst Rocky Desertification Restoration Project) over the past two decades [8,9]. Therefore, a detailed study on karst forest biomass is important for improving the accuracy of estimating Chinese vegetation carbon storages and sequestration potential.…”
Section: Introductionmentioning
confidence: 99%
“…Southwest China contains one of the largest karst regions in the world [8]. Previous studies have assessed the biomass in this region on small and large scales.…”
Section: Introductionmentioning
confidence: 99%
“…Not all studies support the viewpoint that deep root penetration is a necessary strategy for plants adapted to shallow soil environments. For example, recent studies suggest that roots of adapted species in typical karst terrains were restricted to shallow soil layers (Heilman et al, 2009;Kukowski et al, 2013;Ni et al, 2015;Dammeyer et al, 2016;Du et al, 2019). Nie et al (2014a) excavated the coarse root systems of two common species in a karst region of southwest China, and showed that common species, from a variety of habitats, exhibited lateral (almost horizontal) rather than vertical root systems.…”
Section: Introductionmentioning
confidence: 99%
“…shallow soil layer (Heilman et al, 2009;Ni et al, 2015;Nie et al, 2017;Du et al, 2019) where the soil is characterized by higher nutrient content, warmer temperature, and roots require less carbon (Steele et al, 1997). These conflicting viewpoints are due to habitat differences and root plasticity of the plant species (Mulia et al, 2010;Isaac et al, 2014).…”
mentioning
confidence: 99%